Ácaros predadores associados ao ácaro-da-erinose da lichia - Picoli, Pedro Renan Ferreira [UNESP]; Vieira, Marineide Rosa [UNESP]; Silva, Eloisa Aparecida da [UNESP]; Mota, Max Sander de Oliveira da [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2010)
O objetivo deste trabalho foi identificar ácaros predadores em plantas de lichia e correlacionar o desenvolvimento populacional dessas espécies com o do ácaro-da-erinose da lichia, Aceria litchii. A pesquisa foi desenvolvida no Município de Casa Branca, SP, com árvores adultas, de 12 anos de idade, da variedade Bengal. Mensalmente, de agosto de 2008 a setembro de 2009, foram coletadas folhas para avaliação dos níveis populacionais de A. litchii e de ácaros predadores. Foram registrados 6.557 indivíduos da família Phytoseiidae. A espécie mais abundante foi Amblyseius compositus (42,6%), seguida por Phytoseius intermedius (31,2%), Euseius concordis (14,1%), Amblyseius herbicolus (8,8%) e Iphiseiodes zuluagai (3,3%). O desenvolvimento populacional de A. compositus, E. concordis e I. zuluagai correlacionou-se positivamente com o de Aceria litchii, o que indica relação de predação.

The objective of this work was to identify predator mites present in lychee plants and to correlate these species population development with the one of the litchi erineum mite, Aceria litchii. The research was carried out in the county of Casa Branca, SP, Brazil, with mature trees of the Bengal variety, with 12 years old. From August 2008 to September 2009, leaves were collected monthly for the evaluation of A. litchii and predatory mites population levels. Registers were made for 6,557 mites of the Phytoseiidae family. The most abundant species was Amblyseius compositus (42.6%), followed by Phytoseius intermedius (31.2%), Euseius concordis (14.1%), Amblyseius herbicolus (8.8%) and Iphiseiodes zuluagai (3.3%). Population development of A. compositus, E. concordis and I. zuluagai was positively correlated with the one of Aceria litchii, indicating a predation relationship.
Predator mites associated with the litchi erinose mite
Keywords: Aceria litchii; Litchi chinensis; controle biológico; desenvolvimento populacional; Eriophyidae; Phytoseiidae; Aceria litchii; Litchi chinensis; biological control; population development; Eriophyidae; Phytoseiidae